LINKAGE BETWEEN THE USE OF HIRED LABOR AND THE AMOUNT OF ESTICIDE APPLICATION AMONG TANGERINE FARMERS IN THAILAND: A LESSON FOR INDONESIA - Evi Irawan (Widyariset, 2011)
Labor is often neglected in the studies of adoption of agricultural innovation even though it may hinder or facilitate the adoption. This research is to analyze the linkage between the use of hired labor and the amount of pesticides application based on a survey data of 160 tangerine farmers in Thailand. The result shows that there is a positive signiﬁ cant linkage between the use of hired labor and the amount of pesticide application. Main policy implication of this ﬁ nding, especially in the Indonesian context, is that the target of integrated pest management extension or farmers ﬁ eld class should be broadened to include farmers as well as hired laborers.